The formation of a new transnational labour market: Polish labour migration to Vienna in the 1990s - Josef Kohlbacher; Ursula Reeger (European Regional Science Association (ERSA), 1998)
After the fall of the Iron Curtain Austria's position within the framework of Europe's migration league table shifted from a marginal one to that of an appealing "Gateway to the Golden West" with a strong attraction for migrants. So it is not surprising that the inflow of labour force from Poland, Slovakia, the Czech Republic and Hungary was growing during the 1990s. This has led to the formation of a new transnational labour market which includes the eastern regions of Austria and the countries of East-Central Europe. In 1981 5,911 Polish citizens legally lived and worked in Austria. In 1991 the figure was three times as high (18,321), including 8,932 Polish citizens who had taken Austrian citizenship in the meantime. The highest number of labour migrants from Poland (19,421 persons) was registered in 1995. In 1995-96 there was a clear decline in numbers. As the range of information about Polish migration to Austria provided by official census data was quite inadequate we made field research among Vienna's Polish community. The location chosen for the inquiry was the Polish church, one of the favoured meeting points of the Poles. A sample of 408 Poles were interviewed during a spring week in 1993. Naturally, the financial and personal resources of our Institute were too meagre to aspire to an overall study of Vienna's manifold "Polonia". So we tried to concentrate our analysis on some specific topics listed below: - socio-demographic characteristics; - educational background and qualifications level; - labour market position (distribution of migrants among the sectors of the economy, the role of brain drain and its transformation into brain waste, illegal employment); - position on the Viennese housing market; - spatial distribution of the areas of origin in Poland. The main empirical results of the survey which needs stressing are: - the selectivity of Polish immigration by socio-demographic criteria; - the broad variety of family and household structures; - the uneven spatial distribution of the areas of origin of Viennese immigrants; - the overrepresentation of the large urban regions among migration origins; - the importance ot the mainly economic pull factors of the Austrian labour market; - the growing importance of temporary migration; - the high proportion of highly-qualified personnel among migrants; - a broad range of occupations; - a substantial degree of dequalification and brain waste; - an upward occupational mobility which depends on the duration of stay in Vienna; - a close relation of size and standard of dwelling and length of stay in Vienna; - significantly better housing conditions than those of Turkish or Balkanese guest-workers; - the phenomenon of large-scale illegal employment.
Keywords: 330